Discovery and Genetic Mapping of PM1, a Powdery Mildew Resistance Gene in Cannabis sativa L. - Mihalyov, Paul D.; Garfinkel, Andrea R. (Frontiers in Agronomy, 2021)
Powdery mildew is among the most common diseases of both hemp- and marijuana-type cultivated Cannabis sativa. Despite its prevalence, no documented studies have characterized sources of natural genetic resistance in this pathosystem. Here we provide evidence for the first resistance (R) gene in C. sativa, represented by a single dominant locus that confers complete resistance to an isolate of the powdery mildew pathogen Golovinomyces ambrosiae, found in the Pacific Northwest of the United States. Linkage mapping with nearly 10,000 single nucleotide polymorphism (SNP) markers revealed that this R gene (designated PM1) is located on the distal end of the long arm of one of the largest chromosomes in the C. sativa genome. According to reference whole genome sequences and Sanger sequencing, the marker was tentatively placed in a cluster of R genes of the nucleotide-binding site (NBS) and leucine-rich repeat (LRR) protein type. PM1's dominant behavior, qualitative penetrance, and a co-segregating qPCR marker to track its inheritance were confirmed in two separate genetic backgrounds totaling 185 recombinant F1 plants. The goal of this study is to provide a foundation for the discovery and characterization of additional sources of genetic resistance to pathogens that infect C. sativa.